Construction of new selection criteria for Malpura sheep - PASWAN, CHANDAN; GOWANE, G R; PRAKASH, VED; PRINCE, L L L; KUMAR, ARUN (The Indian Journal of Animal Sciences, 2016)
Malpura sheep is one of the heavy mutton type sheep breeds found in semi-arid region of Rajasthan. Objective of the study was to revise the earlier selection criteria and set up a new one for Malpura sheep. The data on 2,995 Malpura sheep descended from 188 sires and 1,021 dams for 11 years (2004–2014) was used to construct the indices using various combination of traits. Genetic parameters were estimated for the traits to be included in the analysis for the data. Estimate of additive genetic variance for 6 month live weight (6WT) was low (h2 = 0.19±0.04). It was recommended to incorporate external germplasm for enhancing the additive genetic variability of the flock. The selection indices were constructed and highest accuracy (51.9%) was observed for the index that involves weaning weight (WWT) and first greasy fleece weight (GFW). Estimated genetic gain after 1 generation post selection was measured to be 221 g in WWT and 81.753 g in GFW. Possibility of direct selection for single trait (6WT) was explored. Results revealed higher response for 6WT (897 g) and high correlated response for other traits such as WWT (0.566 kg), ADG1 (5.601 g), ADG2 (3.132g) and GFW (26.52 g) as compared to index selection. As milk yield of dam has strong influence on pre-weaning gain, preliminary selection at weaning followed by direct selection at 6 month age based on single trait selection (6WT) was recommended as selection criteria.